From Syntax to Stylistics: A Case Study of Selected Haikus - Sarac Durgun, Hatice Sezgi (2022)
A writer’s style reflects how textual meaning-making processes are achieved through a literary text's form, which includes various textual strategies employed. Available literature suggests that almost every linguistic theory takes the sentence structure as a combination of ‘form’ and ‘content’, whose taxonomic amplifications provide a springboard for description that leads to a more comprehensive extension of linguistic analyses revealing the semantic and symbolic aspects of language making up a text. Hence, although textual analysis may start by identifying its form and content, a comprehensive approach that engulfs a text’s syntactic and semantic aspects provides a broader perspective. Keeping these in mind, this study is based on the premise that structural analysis enables the identification of the poet’s recurrent method of composing different literary texts of the same genre and guides analysts to semantic interpretations. Examining the poetic language of a selection of haikus written by Wright, with a focus on the syntactic and semantic identifications, it is observed that the poet has an uncompromising style toward utilizing a pattern with minor alterations to construct various poems. The poet achieves an effective diction using a restricted number of lexical and grammatical items, which fits into the terseness of haikus, a poetic form known for its brevity and conciseness.
Keywords: syntax; pedagogy; stylistics; poetry; haiku; literature; linguistics